Crime, addiction and the regulation of gambling - Spapens, A. C. <<[Hrsg.]>>; Spapens, Toine <<[Hrsg.]>>; Littler, Alan <<[Hrsg.]>> (Martinus Nijhoff Publishers, 2008)
Crime and addiction : their role in the debate between the European Commission and the Netherlands -- Penetration of criminals into the legal betting and gaming sector -- Improper use of gambling for illegal activities -- Crime in relation to gamblers
Includes index